Modeling and optimization of a honeycombed adsorbent bed for efficient moisture capture. (5th January 2022) - Wang, Wenwen; Pan, Quanwen; Wang, Ruzhu; Ge, Tianshu
Highlights: Provide understanding of mass transfer in the adsorption process. Small aspect ratio of air channel and thin sorbent layer for optimal bed structure. A transient 3-D heat and mass transfer model was developed and simulated. Fractional moisture capture is to evaluate the utilization extent of the sorbent. Abstract: Adsorption-based atmospheric water harvesting has received significant interest owing to its promise of decentralized water supply and a wide applicability. In this study, the adsorbent bed is specially designed and optimized for efficient moisture capture. A transient three-dimensional non-equilibrium model has been developed that takes both internal and external mass transfer resistances into account. It is found that the simulation results agree better with the experimental results, which indicates the reliability of the model. Then this model was applied to investigate the influence of the adsorbent bed structure, and the operating parameters on the transient distributions of the adsorbent temperature, adsorption kinetics, dynamic up-taken moisture capture, mass transfer resistance and relative capture efficiency of the adsorbent bed. ASLi30 (Activated carbon fiber + Silica gel + 30 wt% LiCl)-vapor is selected as the working pair. It has been found that generally, the effects of the air channel aspect ratio on the investigated indexes are negligibly small. A thinner layer thickness and a smaller air channel length characterize an excellent moisture capture, small vapor transport resistance and faster adsorption kinetics. By considering different parametric variations for performance optimization and the effect of operating conditions, these results provide important insights and design guidelines of adsorbent bed for efficient moisture capture.